Characterization of a NDM-1- Encoding Plasmid pHFK418-NDM From a Clinical Proteus mirabilis Isolate Harboring Two Novel Transposons, Tn6624 and Tn6625 - Dong, Dandan; Li, Manli; Liu, Zhenzhen; Feng, Jiantao; Jia, Nan; Zhao, Hui; Zhao, Baohua; Zhou, Tingting; Zhang, Xianglilan; Tong, Yigang; Zhu, Yuanqi (Frontiers in Microbiology, 2019)
Acquisition of the blaNDM-1 gene by Proteus mirabilis is a concern because it already has intrinsic resistance to polymyxin E and tigecycline antibiotics. Here, we describe a P. mirabilis isolate that carries a pPrY2001-like plasmid (pHFK418-NDM) containing a blaNDM-1 gene. The pPrY2001-like plasmid, pHFK418-NDM, was first reported in China. The pHFK418-NDM plasmid was sequenced using a hybrid approach based on Illumina and MinION platforms. The sequence of pHFK418-NDM was compared with those of the six other pPrY2001-like plasmids deposited in GenBank. We found that the multidrug-resistance encoding region of pHFK418-NDM contains ΔTn10 and a novel transposon Tn6625. Tn6625 consists of ΔTn1696, Tn6260, In251, ΔTn125 (carrying blaNDM-1), ΔTn2670, and a novel mph(E)-harboring transposon Tn6624. In251 was first identified in a clinical isolate, suggesting that it has been transferred efficiently from environmental organisms to clinical isolates. Genomic comparisons of all these pPrY2001-like plasmids showed that their relatively conserved backbones could integrate the numerous and various accessory modules carrying multifarious antibiotic resistance genes. Our results provide a greater depth of insight into the horizontal transfer of resistance genes and add interpretive value to the genomic diversity and evolution of pPrY2001-like plasmids.